2016
DOI: 10.1080/13636820.2016.1231215
|View full text |Cite
|
Sign up to set email alerts
|

Promoting VET teachers’ innovative behaviour: exploring the roles of task interdependence, learning goal orientation and occupational self-efficacy

Abstract: Changing employer demands, new technological and pedagogical insights are examples of developments which urge Vocational Education and Training (VET) institutes to continually renew and innovate their educational programmes. This, in turn, requires teachers to show innovative behaviour. Our study focuses on the effects of task interdependence on VET teachers' innovative behaviour. In addition, the mediating roles of learning goal orientation and occupational self-efficacy in this relationship are examined. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 61 publications
(61 reference statements)
3
25
0
Order By: Relevance
“…It enables them to find ideas and develop them further through the small-scale application of these ideas. Moreover, previous research also found that in jobs with fully autonomous, employees tend to participate more in knowledge sharing (P. Runhaar et al, 2016). As a result, research identified job autonomy as a strong relationship with employee innovative work behaviour (Messmann et al, 2017;Rahman, Panatik, & Alias, 2014;Ramamoorthy et al, 2005;Sharifirad, 2013;Thurlings et al, 2015).…”
Section: Job Autonomymentioning
confidence: 84%
See 1 more Smart Citation
“…It enables them to find ideas and develop them further through the small-scale application of these ideas. Moreover, previous research also found that in jobs with fully autonomous, employees tend to participate more in knowledge sharing (P. Runhaar et al, 2016). As a result, research identified job autonomy as a strong relationship with employee innovative work behaviour (Messmann et al, 2017;Rahman, Panatik, & Alias, 2014;Ramamoorthy et al, 2005;Sharifirad, 2013;Thurlings et al, 2015).…”
Section: Job Autonomymentioning
confidence: 84%
“…Relatively few studies focus specifically on school teachers' innovative work behaviour and its determinants (Klaeijsen et al, 2017;Thurlings et al, 2015). Studies among school teachers point at the effects of different factors such as function or task, and self-efficacy (Fairuz et al, 2013), work engagement (P. Runhaar, Bednall, Sanders, & Yang, 2016), job control and creative requirements (Binnewies & Gromer, 2012), and openness, motivation, job satisfaction, and interaction within the job (G. Gorozidis & Papaioannou, 2014;Serdyukov, 2017;Thibaut, Knipprath, Dehaene, & Depaepe, 2018). Despite these studies show that different motivational factors may contribute to innovative work behaviour.…”
Section: Innovative Work Behaviourmentioning
confidence: 99%
“…This means not only that individual tasks in a work team need to be interdependent, where everyone's behavior contributes to the common goal, but also team members consciously perceive this interdependence. In vocational learning environments, we expect students to be more motivated when they realize their contribution to the common good (Runhaar et al 2016). However, a difference with profit-driven collaborative relations is that students are in a more dependent position and therefore the effects of dependence on others will affect joint production motivation to a lesser extent.…”
Section: Joint Production Motivation and Social Resiliencementioning
confidence: 99%
“…Current research is focused on the issues of VET teachers' professional development within modern society development. In particular, Day (2017) investigated competence-based education and VET teachers professional development; Runhaar, Bednall, Sanders and Yang (2016) studied issues of promoting VET teachers' innovative behaviour; Oser, Salzmann and Heinzer (2009) and Arifin, Rasdi, Anuar and Omar (2017) investigated different aspects of measuring competencies of VET teachers; Nickolaus (2007) studied the impact of teachers' competencies on the quality of VET; Fortmüller and Kramer (2014) proved the intermediate correlation between social competence of the VET teachers and their perception of working relations with students as the social burden, etc.…”
Section: Introductionmentioning
confidence: 99%